Funcionamiento de la tecnología limpia Oilmate para el mejoramiento del rendimiento de motores en vehículos y maquinaria pesada. (2014)
This paper describes the environmental benefits that can bring incorporating clean industry, specifically the automotive, heavy machinery and transport technologies. These environmental benefits can reduce the negative environmental impact generated by various industrial processes on such activities. For this work, the product OilMate, a clean technology that is implemented in cars, trucks, heavy machinery, etc., and efficiently reduces the amount of hazardous waste generated and improves the quality of emissions generated in the equipment described.